2019
DOI: 10.7759/cureus.4949
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus Infection and Tetralogy of Fallot: An Unusual Association in a Three-month-old Baby

Abstract: Congenital cytomegalovirus (cCMV) infection is the leading cause of infant morbidity and mortality worldwide. Despite being associated with significant neurological sequelae in infected infants, it remains an under-recognized public health entity. Symptomatic newborns most frequently display hepatosplenomegaly, petechiae, jaundice, microcephaly, intrauterine growth restriction, chorioretinitis, purpura, and seizures. Progressive sensorineural hearing loss is the most prominent adverse outcome of both symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In our study, body height was more affected in children with TOF. It has been reported that TOF affects body height severer than acyanotic CHD, might be due to the long period of hypoxemia 19 . The four defects caused by TOF results in short of blood in lung to get oxygen, and oxygen-poor blood effects the metabolic in body tissues, finally leads to the defects of growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, body height was more affected in children with TOF. It has been reported that TOF affects body height severer than acyanotic CHD, might be due to the long period of hypoxemia 19 . The four defects caused by TOF results in short of blood in lung to get oxygen, and oxygen-poor blood effects the metabolic in body tissues, finally leads to the defects of growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases it is associated with another heart lesion and clinical presentation is dependent on the associated lesions. In patient with no associated lesion, presentation is usually in adulthood with RV dysfunction and heart failure [4].…”
Section: Discussionmentioning
confidence: 99%